Analisis Pengaruh User Experience Ride Sharing Application Terhadap Citra Merek Pada Pengguna Android dan iOS - Yudhistira Serdiansyah Alrio; Agi Putra Kharisma; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
User experience is gained by the consumers through the participation and involvement when using the appications. It has a possibility to be captured more strongly than consumers experience from conventional media. The aim of this research is to determine whether there is influence of user experience on brand image, the influence's level of user experience on the brand image, and also the influence of user experience on the brand image. This research used two methods, there are De Angeli method which used seven dimensions for measuring the user experience and also Keller method which used three dimensions for measuring the brand image. The data source used in this study was a primary data which derived from quitionnaire. Based on the data analysis, it is known that the user experience on the ride sharing application had no effect toward the brand image of ride sharing application, then the high correlation level of user experience towards the brand image explained that the user experience was able to influence on the brand image. The user experience of Android users had an effect amount 29.40% and 52.10% for iOS users on the brand image.